FORMS OF COHESION IN CONFINEMENT INSTITUTIONS - E. D. Slobodenyuk; E. D. Volkova (Russian Journal of Economics and Law)
Objective: to identify the diversity of cohesion forms in confinement institutions.Methods: qualitative analyses based on in-depth semi-structured interviews.Results: the study included adaptation of Western methodologies of the cohesion phenomenon analysis to the Russian reality, and operational- ization of the moral bases of group cohesion. This served as the bases for designing a guide for in-depth semi-structured interviews; 10 interviews were conducted with people recently released from general and strict regime colonies. Content analysis of the interviews revealed a number of structural sections that demonstrate the diversity of cohesion forms, alongside with one that is most meaningful to the prisoners and therefore the most well perceived and articulated by respondents. Analysis of the latter allowed to identify a set of groups showing different degree and nature1 This work was supported by the Russian Scientific Foundation under Grant № 14-18-03784.271Уголовное право и криминологияCriminal law and criminologyАктуальные проблемы экономики и права. 2015. № 4Actual Problems of Economics and Law. 2015. No. 4of cohesion. By the degree of cohesion one can identify the poorly cohesive groups ("louts"), moderately cohesive ("reds", "thieves") and highly cohesive ("fighters"). By the nature of cohesion in the prisoners’ community, there are both groups united on the basis of social morality ("reds", "thieves") and groups demonstrating a high degree of cohesion based on the social justice morality ("fighters"). A detailed analysis of the latter group also showed that the cohesion can have both traits of morality, social justice, and features of social order moral.Scientific novelty: using the socio-psychological theory of the moral motives in determining the bases of cohesion.Practical significance: the research results can be applied for the development of socio-psychological techniques for the penal system reform.